2017
DOI: 10.18203/2394-6040.ijcmph20174224
|View full text |Cite
|
Sign up to set email alerts
|

Health care seeking behaviour of women during pregnancy in rural south India: a qualitative study

Abstract: Background: Antenatal care is an important indicator in any health system. Through our study we intended to assess the perception of pregnant women regarding health seeking behaviour and awareness about complications during pregnancy. Methods: A qualitative study was carried out in August 2016, among the 41 pregnant women over 27 weeks of gestation in a rural area of south India. Women were selected randomly from the routine surveillance system maintained by Pondicherry Institute of Medical Sciences – Rural He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Similar findings were obtained in a study done by Vincent et al ., where among the postnatal mothers, 82.4% of them consumed IFA tablets for >90 days. [18] Non-compliance in the IFA medication in some of them would have been due to the adverse effects like nausea and vomiting. Similar findings were obtained in studies conducted by Jha et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were obtained in a study done by Vincent et al ., where among the postnatal mothers, 82.4% of them consumed IFA tablets for >90 days. [18] Non-compliance in the IFA medication in some of them would have been due to the adverse effects like nausea and vomiting. Similar findings were obtained in studies conducted by Jha et al .…”
Section: Discussionmentioning
confidence: 99%
“…and Saha et al ., where only 50% and 60% of the participants had adequate antenatal visits, respectively. [131822] These variations may have been due to the heterogeneity in the socio-demographic characteristics of the study participants and the availability and accessibility of health services in the respective study areas.…”
Section: Discussionmentioning
confidence: 99%
“…This is usually the case in rural areas as shown in the study by Vincent et al in Pondicherry which showed most of the women in rural area seek care in government facility due to its availability, accessibility and affordability as per the qualitative study conducted by them. 13 Mini and Sidhiq in their study assessing pattern of antenatal care among women utilising a tertiary care centre in government sector for delivery, found that 59% had antenatal care services from Government institutions and the remaining 41% from private centres.…”
Section: Discussionmentioning
confidence: 99%
“…From the electronic database called CHIMS (Community Health Information Management System) which maintains the health-related details of these individuals belong to the ten villages, patients with diabetes and hypertension were line-listed, approached, and invited to participate in the study. [ 19 20 21 ] after getting consent, data was collected in the concerned villages of the participants by setting up a camp with a pretested proforma. Plasma and serum were collected at fasting state and transferred to the main campus situated 30 km away, which has the NABL accredited labs (National Accreditation for Testing and Calibration Laboratories).…”
Section: Methodsmentioning
confidence: 99%